Estimation and Comparison of Bio-Oil Components from Different Pyrolysis Conditions - Lyu, Gaojin; Wu, Shubin; Zhang, Hongdan (Frontiers in Energy Research, 2015)
In the case of development and utilization of bio-oils, a quantitative chemical characterization is necessary to evaluate its actual desired characteristics for downstream production. This paper describes an analytical approach for the determination of families of lightweight chemicals from bio-oils by using GC-MS techniques. And on this basis, new explorations in the field of influence factors, such as feedstocks, pyrolysis temperatures, and low temperature pretreatment, on the composition and products yields of bio-oil were further investigated. Up to 40% (wt.%) of the bio-oil is successful quantified by the current method. Chemical functionalities in the bio-oil correlates strongly with the original feedstocks because of their different chemical compositions and structure. Pyrolysis temperature plays a vital role in the yields of value-added compounds, both overall and individually. Higher temperature favored the generation of small aldehydes and acids, accompanied by a reduction of phenols. The optimal temperatures for maximum furans and ketones yields were 520 oC and 550 oC, respectively. The low temperature pretreatment of biomass has a good enrichment for the lightweight components of the bio-oils. In this case, much higher amounts of compounds, such as furans, ketones, and phenols were produced. Such a determination would contribute greatly to a deeper understanding of the chemical efficiency of the pyrolysis reaction and how the bio-oils could be more properly utilized.